The Analysis of Character Identity in “The Woman in The Window” Novel by A. J. Finn - Nawawi, Imam; Satria, Robby (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2024)
This study delves into the exploration of character identity within A.J. Finn's psychological thriller